Genomic Comparative Analysis of Two Multi-Drug Resistance (MDR) Acinetobacter baumannii Clinical Strains Assigned to International Clonal Lineage II Recovered Pre- and Post-COVID-19 Pandemic - Traglia, German Matias (2023)
Background: After the emergence of COVID-19, numerous cases of A. baumannii/SARSCoV-2 co-infection were reported. Whether the co-infecting A. baumannii strains have distinctivecharacteristics remains unknown. Methods and Results: A. baumannii AMA_NO was isolated in2021 from a patient with COVID-19. AMA166 was isolated from a mini-BAL used on a patient withpneumonia in 2016. Both genomes were similar, but they possessed 337 (AMA_NO) and 93 (AMA166) unique genes that were associated with biofilm formation, flagellar assembly, antibiotic resistance, secretion systems, and other functions. The antibiotic-resistance genes were found within mobile genetic elements. While both strains harbored the carbapenemase-coding gene blaOXA-23, only the strain AMA_NO carried blaNDM-1. Representative functions coded for by virulence genes are the synthesis of the outer core of lipooligosaccharide (OCL5), biosynthesis and export of the capsular polysaccharide (KL2 cluster), high-efficiency iron uptake systems (acinetobactin and baumannoferrin), adherence, and quorum sensing. A comparative phylogenetic analysis including 239 additional sequence type (ST) 2 representative genomes showed high similarity to A. baumannii ABBL141. Since the degree of similarity that was observed between A. baumannii AMA_NO and AMA166 is higher than that found among other ST2 strains, we propose that they derive from a unique background based on core-genome phylogeny and comparative genome analysis. Conclusions: Acquisition or shedding of specific genes could increase the ability of A. baumannii to infect patients with COVID-19.